(1390) an integrated frame - work for experimental investigation by simulation models إطار عمل متكامل للبحث التجريبي بواسطة نماذج المحاكاة - khorshid, motaz (The Institute Of National Planning., 2018)
The use of computer simulation technique to conduct artificial experiments on numerical models of' complex systems, is an increasingly important tool in many disciplines today. Computer simulation offers many features that make it an attractive experimental method-for studying management and economic systems,